ANALISIS BIBLIOMETRIK ATAS PENELITIAN BELANJA PERPAJAKAN MENGGUNAKAN APLIKKASI VOSVIEWER - Diperhatikan Halawa; Fitriana Fitriana; Rachmat Agus Santoso (Jurnal Akuntansi dan Pajak, 2024)
Tax spending leads to reduced tax revenue from certain taxpayers. It has been a lot to do the study of this field. The purpose of this study is to analyze the classification of tax expenditure research articles, identify topic trends in tax expenditure research, and analyze opportunities for tax spending research topics in the future. The research method used a five-step method of bibliometric analysis and data analysis was used vosviewer application. Article searches were used through data from Scopus with the keyword "tax expenditure" in the title section of the Scopus database published from 1977 – 2022 (a period of 45 years) and obtained 74 articles. The results of the first VOSviewer analysis, network visualization, show that the tax expenditure research article can be classified into four clusters. The first cluster consists of 6 keywords, the second cluster consists of 10 keywords, the third cluster consists of 9 keywords, and cluster four consists of 10 keywords. The results of VOSviewer's second analysis, overlay visualization, show that the trends in research topics are economics, tax expenditure, econ, and management. The results of the third VOSviewer analysis, density visualization, show that there are still many rarely studied so that it becomes an opportunity for research topics in the future. Keywords: tax spending, bibliometric analysis, Publish or Perish, VOSviewer, Scopus